2022
DOI: 10.3390/biomedicines10061360
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation Profile in Myasthenia Gravis Patients: Perspectives for Tailoring Anti-Complement Therapy

Abstract: The complement system plays a key role in myasthenia gravis (MG). Anti-complement drugs are emerging as effective therapies to treat anti-acetylcholine receptor (AChR) antibody-positive MG patients, though their usage is still limited by the high costs. Here, we searched for plasma complement proteins as indicators of complement activation status in AChR-MG patients, and potential biomarkers for tailoring anti-complement therapy in MG. Plasma was collected from AChR-MG and MuSK-MG patients, and healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 39 publications
(65 reference statements)
4
13
0
Order By: Relevance
“…Despite the clinical efficacy of its inhibition, roles of the complement system in MG are still poorly understood, but in vivo data on its activation in MG patients are increasing. Iacomino et al reported increased levels of C3, C3b and C5a in the plasmas of patients with AChR‐Ab + MG, but not in MuSK‐Ab + MG patients, which is in line with our findings [15]. Additionally, they also found no correlation of plasma levels of the altered complement components (C2, C3, C3b, C5 and C5a) with disease severity or AChR‐Ab titres.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the clinical efficacy of its inhibition, roles of the complement system in MG are still poorly understood, but in vivo data on its activation in MG patients are increasing. Iacomino et al reported increased levels of C3, C3b and C5a in the plasmas of patients with AChR‐Ab + MG, but not in MuSK‐Ab + MG patients, which is in line with our findings [15]. Additionally, they also found no correlation of plasma levels of the altered complement components (C2, C3, C3b, C5 and C5a) with disease severity or AChR‐Ab titres.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the clinical efficacy of its inhibition, roles of the com- which is in line with our findings [15]. Additionally, they also found no correlation of plasma levels of the altered complement compo- Studies in such larger series could additionally focus on the various AChR epitopes recognized by the patients' Abs, which can vary between MG subgroups [23] and might affect complement activation.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, it has been reported that plasma C5 levels were significantly lower in anti-AChR-antibody-positive MG patients compared with those in controls. 10 C5 is located upstream of sC5b-9, 3 and lower C5 levels accompanied by high sC5b-9 levels observed in the patients with MG in the present study may indicate the decomposition of C5 after an elevation of sC5b-9, namely the activation of the terminal complement pathway. C5b is primarily involved in the formation of the membrane attack complex, whereas C5a shows potent biological activity in the development of inflammatory sequelae such as the promotion of leukocyte chemotaxis, enhancement of neutrophil-endothelial cell adhesion and vascular permeability, induction of granule secretion by phagocytes, and production of various cytokines.…”
Section: Discussionsupporting
confidence: 54%
“…Lacomino et al reported plasma C5a levels were higher in AChR-antibody-positive MG compared with those in controls, although C5a did not correlate with disease severity. 10 In a mouse model of autoimmune MG, the susceptibility to T A B L E 1 Relation between complement/their regulators and clinical profiles in MG C1q (μg/mL) C5 (μg/mL) C5a (ng/mL) sC5b-9 (μg/mL) Ba (μg/mL) CFH (mg/mL) Sex (female vs. male) 7.9 ± 3.4 vs. disease was comparable between the C5a receptor-knockout and wildtype mice based on antibody and lymphocyte proliferation responses to AChR. 17 Further studies are warranted to elucidate the role of C5a in the pathogenesis of human MG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation